Study of Surface Modification of ZrO2/SiO2 Nanocomposites with Aluminum Zirconium Coupling Agent - Li, Wei; Zheng, Shaohua; Ma, Shiyu; Ding, Haiyang; Jiao, Da; Cao, Bingqiang (Asian Journal of Chemistry, 2010)
In this studies, the ZrO2/SiO2 composite nanoparticles are prepared by situ-modified method and the ZrO2/SiO2 composite nanoparticles are modified by aluminum zirconium coupling agent. By using the particle size analysis, it is confirmed that the mean particle size of modified ZrO2/SiO2composite nanoparticles is 55 nm and its distribution is uniform. The dispersion of modified ZrO2/SiO2composite nanoparticles is analyzed by the absolute value of ZrO2/SiO2nanoparticles Zeta potential. Through transmission electron micrograph (TEM) observation, it is found that aluminum zirconium coupling agent improve the dispersibility of ZrO2/SiO2composite nanoparticles. The hydroxyl groups on the surface of ZrO2/SiO2composite nanoparticles can interact with hydroxyl groups of aluminum zirconium coupling agent and an organic coating layer is formed. The formed covalent bands are testified by Fourier transform infrared spectra (FT-IR). The dispersion stabilization of modified ZrO2/SiO2composite nanoparticles in lubricating oil is significantly improved due to the introduction of grafted polymers on the surface of nanoparticles.